(untitled) (Nigerian Journal of Technology, 2018)
The assessment of the durability of twelve cylindrical samples of black cotton soil, a well-known problem soil, stabilized with a combination of 4%lime and 16% sawdust ash were carried out in laboratory using the methods of [1] and that recommended by [2] and [3]. The results showed that the unconfined compressive strength of the samples under varying curing and soaking conditions ranged from 1217kPa to 265kPa while the durability indices were 59.51% and 59% respectively. Thus, the stabilizers have elevated the otherwise non-durable soil into the marginally durable zone. Keywords: Black cotton soil, Durability, Sawdust ash, Stabilisation, Unconfined compressive strength http://dx.doi.org/10.4314/njt.v38i1.10